Global cascade of care for chronic hepatitis C virus infection: A systematic review and meta‐analysis. Issue 10 (31st July 2021) - Yousafzai, Mohammad T.; Bajis, Sahar; Alavi, Maryam; Grebely, Jason; Dore, Gregory J.; Hajarizadeh, Behzad
Abstract: The World Health Organization 2030 targets for hepatitis C virus (HCV) elimination include diagnosing 90% of people with HCV and treating 80% of people diagnosed with HCV. This systematic review assessed reported data on the HCV care cascade in various countries and populations, with a focus on direct‐acting antiviral (DAA) treatment uptake. Bibliographic databases and conference presentations were searched for studies reporting the HCV care cascade (DAA treatment uptake was a requirement) among the overall population with HCV or sub‐populations at greater risk of HCV. Population‐based studies, with participants representative of a city, province/state or country were eligible. Twenty eligible studies were included, reporting HCV care cascade in 28 populations/sub‐populations from 11 countries. DAA treatment uptake at national levels was reported from Iceland (95%), Egypt (92%), Georgia (79%), Norway (18%) and Sweden (8%), and at sub‐national levels from the Netherlands (52%), Canada (50%), the United States (29%) and Denmark (5%). Among people with HIV‐HCV co‐infection, DAA treatment uptake was 62% in Canada, 44% in the Netherlands, 21% in Switzerland and 18% in the United States. Among people who inject drugs, DAA treatment uptake was 50% in Georgia, 40% in Canada, 37% in Australia and 13% in the United States. Data among people experiencing homelessness were only available from the United States (treatment uptake: 12%–14%). We found no eligible study reporting HCV care cascade data in prisons. Relatively few countries reported HCV care cascade at the national level. DAA treatment uptake was widely varied across populations/sub‐populations, with higher rates reported in recent years.